2009
DOI: 10.1021/ol9016657
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic Access to Versatile Epoxyquinol Synthons

Abstract: The enantiomerically pure and readily available metabolites 10-12 have been converted over four simple steps into the epoxyquinol derivatives 22-24, respectively. Compounds 23 and 24 or their immediate precursors have been exploited in efficient total syntheses of (-)-bromoxone (ent-1), (-)-epiepoformin (ent-2), (-)-harveynone (4), (+)-panepophenanthrin (6), and (+)-hexacyclinol (9).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 43 publications
1
34
0
2
Order By: Relevance
“…In keeping with earlier observations, [2,3] reaction of compound 7 with freshly prepared sodium methoxide in THF at ambient temperatures gave epoxide 8, which was obtained as a white, crystalline solid in 99 % yield. The selectivity of this epoxide-forming step is attributed to the more favorable orientation of the non-allylic hydroxy group (over its allylic counterpart) for participation in the required internal nucleophilic displacement reaction.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…In keeping with earlier observations, [2,3] reaction of compound 7 with freshly prepared sodium methoxide in THF at ambient temperatures gave epoxide 8, which was obtained as a white, crystalline solid in 99 % yield. The selectivity of this epoxide-forming step is attributed to the more favorable orientation of the non-allylic hydroxy group (over its allylic counterpart) for participation in the required internal nucleophilic displacement reaction.…”
Section: Resultssupporting
confidence: 85%
“…Several attempts to improve the selectivity of this reductive cleavage process, including those involving an examination of variations in reaction solvent and temperature as well as the nature of the reducing agent, failed. Treatment of the 2.5:1 mixture of monoethers 4 and 5 with N-bromosuccinimide (NBS) in wet THF under conditions used in our earlier studies [2,3] Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We point out the first real material examples in the class of three-dimensional organic crystals hosting isolated Dirac nodes in the electronic structure: C 6 H 7 ClO 3 25 , C 10 H 10 Br 2 Cl 3 NO 2 26 , C 12 H 13 NO 2 27 , C 13 H 12 N 2 O 28 , C 9 H 10 F 3 NO 29 , and C 10 H 12 BrNO 30 . It will be shown that the found Dirac nodes are a consequence of the orthorhombic crystal structure of the space group P 2 1 2 1 2 1 (#19).…”
Section: Introductionmentioning
confidence: 99%